Impacts of seasonal dynamics on cyanobacterial proliferation and cyanotoxins bioaccumulation in fish species: Comparative study of aquaculture fishponds in Nigeria and South Africa - Bassey, Odo Jones (My University, 2025)
Aquaculture production plays a pivotal role in advancing Sustainable Development Goals (SDGs), particularly those focused on food security, economic growth, livelihoods, sustainable production, biodiversity conservation, and improved nutrition. Locally produced fish from aquaculture ponds serve as an affordable and accessible protein source in countries like Nigeria and South Africa. However, the rise of cyanobacterial harmful algal blooms (CyanoHABs) poses a serious challenge to the sustainability of fish culture production and human health. In the aquaculture ecosystem, the consequences of these blooms have triggered widespread interest due to cyanotoxin bioaccumulation in cultured fish species. In tropical regions, especially in Africa, there is a paucity of research investigating the temporal drivers of cyanobacterial biomass in aquaculture fishponds. Cyanobacteria are integral to the pond food chain, yet their seasonal dynamics factors and influencing factors remain poorly understood. This knowledge gap is particularly critical as these factors significantly impact aquaculture productivity and the risks associated with cyanobacterial blooms. Therefore, this study investigated the impact of seasonal dynamics on cyanobacterial proliferation and cyanotoxin bioaccumulation in cultured fish. A comparative study design between small-scale commercial fishponds located in Nigeria (NGA) and South Africa was employed in this study. A total of six fishponds located in Calabar Municipality, Cross River State, Nigeria, and Duthuni, Vhembe District, Limpopo Province, South Africa (SA), were selected. Water and Clarias gariepinus (African catfish) samples were collected from each fishpond at seasonal intervals (SA - summer, winter, NGA - dry and wet seasons). Seasonal variations in water quality parameters were observed in NGA and SA fishponds. Cyanotoxins analysis was carried out using the Liquid Chromatography-Mass Spectrometry (LCMS). The results of the study revealed that elevated temperatures (>20°C) were consistent during dry, wet, and summer seasons, with a notable winter decrease (16.5°C) at Duthuni, South Africa. Dissolved oxygen (DO) and electrical conductivity (EC) levels were consistently low across seasons, while total dissolved solids (TDS) peaked during winter in South Africa (125–193.2 mg/L) and were lower in Nigeria (15.9–37.7 mg/L). Nutrients, particularly nitrite and nitrate, peaked in Nigeria during wet (10.42 mg/L) and dry (6.45 mg/L) seasons, while South African fishponds exhibited lower concentrations in both summer and winter. The study revealed that cyanobacterial biomass and cyanotoxins in fishponds were not driven by seasonal factors like warmer temperatures or precipitation. Cyanobacteria biomass was predominantly influenced by management practices, including feeding, fertilization, nutrient levels, water volume, stocking density, water exchange, and retention time. The LCMS analysis revealed that the microcystin variant MC-RR was absent in fish tissue, while MC-YR was detected in the intestines, gills, muscles, and liver. The highest concentration of 20.9 μg/g was found in the liver. Additionally, untargeted LC-MS identified a broader range of cyanotoxins, including aeruginosins, anabaenopeptins, microcystins, and microginins, in the water samples and fish tissue. These findings underscore the critical influence of fishpond management practices on cyanobacterial dynamics and cyanotoxin bioaccumulation. This study highlights the need for targeted interventions to mitigate cyanotoxins risks in aquaculture systems. Understanding and addressing these factors are essential for ensuring the sustainability of aquaculture production and safeguarding public health in tropical regions.
PhDENV
Department of Geography and Environmental Sciences
Keywords: UCTD